Pre-Clinical Studies of Inactivated Polivalent Vaccine Against Hemorrhagic Fever with Renal Syndrome - A. A. Sinyugina; T. K. Dzagurova; A. A. Ishmukhametov; M. V. Balovneva; S. S. Kurashova; N. A. Korotina; M. S. Egorova; E. A. Tkachenko (Эпидемиология и вакцинопрофилактика)
Relevance. Hemorrhagic fever with renal syndrome (HFRS) is a non-transmissible viral zoonosis widespread in Eurasia, and in Russia it occupies a leading position among zoonotic viral infections and one of the first places among all natural focal human diseases. Aim. Obtaining evidence of the safety, quality and efficacy of a polyvalent vaccine against HFRS as a result of its preclinical studies using scientific assessment methods that meet the requirements and rules of good laboratory practice. Materials and methods. For preclinical studies of the polyvalent vaccine against HFRS, the materials and methods were used in strict accordance with the requirements of the regulatory documents, as well as previously described methods used to control the vaccine at the technological stages of its manufacture. Results. The data obtained as a result of preclinical studies of the polyvalent vaccine agains HFRS indicate a high immunogenicity and stability of the vaccine, the absence of: acute and chronic toxicity, allergenic, immunotoxic and mutagenic, as well as toxic effects on the reproductive organs of animals, embryo development and offspring, born to females who received the vaccine within 20 days of gestation. Conclusion. The obtained results of preclinical studies comply with the requirements for immunobiological medical preparations designed for humans, and are the basis for conducting the 1st phase of clinical trials the polyvalent vaccine against HFRS.